Sistemas de cobre : agentes quimioterápicos potenciais para combater o crescimento de tumores malignos - Santos, Mirian Paula dos (2007)
In order to find inorganic compounds with biological properties as chemotherapeutic agents that could increase the possibilities in the treatment of some diseases, copper complexes with Schiff base ligands were prepared and characterized. In this work we prepared 63 compounds, being 19 symmetrical tetradentate Schiff base ligands and their respective copper complexes, 16 copper complexes with unsymmetrical tetradentate Schiff base ligands and 9 copper complexes with tridentate Schiff base ligands derived from ethylenediamine, trans-1,2-diaminocyclohexane and orto-phenylenediamine, with salicylaldehyde or substituted salicylaldehyde. All were characterized by vibracional spectroscopy (infrared), electronic spectroscopy (ultraviolet-visible) and others methods such as solubility, melting points. Some complexes were studied by cyclic voltammetry and magnetic susceptibility. The structures of [Cu(3-MeOsalen)], [Cu(3- EtOsalen)] and [Cu(4-DEAsalen)], have been determined by single crystal X-ray diffraction. The cytotoxicity of the symmetrical complex [Cu(4-DEAsalen)], was evaluated using HPV-16 and HPV-18 infected cells. Cytotoxicity tests using spleen cells of BALB/c mice were performed using 5 tridentate complexes. The characterization results show that the synthesis had been successful with good yields. The effect of the substitution on the aromatic ring was compared for compounds within a series and between different series.